Exploiting neighbourhood structural features for change detection. Issue 4 (3rd April 2023) - Wang, Mengmeng; Han, Zhiqiang; Yang, Peizhen; Zhu, Bai; Hao, Ming; Fan, Jianwei; Ye, Yuanxin
ABSTRACT: In this letter, a novel method for change detection is proposed using neighbourhood structure correlation. Because structure features are insensitive to the intensity differences between bi-temporal images, we perform the correlation analysis on structure features rather than intensity information. First, we extract the structure feature maps by using multi-orientated gradient information. Then, the structure feature maps are used to obtain the Neighbourhood Structural Correlation Image (NSCI), which can represent the context structure information. In addition, we introduce a measure named matching error, which can be used to improve neighbourhood information. Subsequently, a change detection model based on the random forest is constructed. The NSCI features and matching error (ME) are together used as the model inputs for training and prediction. Finally, the decision tree voting is used to produce the change detection result. To evaluate the performance of the proposed method, it is compared with three state-of-the-art change detection methods. The experimental results on two datasets demonstrate the effectiveness and robustness of the proposed method.